Wachstum bei Störungen der Schilddrüsenfunktion im Kindes- und Jugendalter: Störungen der Schilddrüsenfunktion und Wachstum = Growth in thyroid disorders in childhood and adolescence : Thyroid dysfunction and growth - Bettendorf, Markus (Monatsschrift Kinderheilkunde, 2016)
BackgroundDisorders of the thyroid function of mother and child can not only irreversibly inhibit maturation of the central nervous system, but may also affect growth and puberty.ObjectivesReview of the consequences of thyroid function disorders on the growth of children and adolescents and the relevance of adequate treatment.Materials and MethodsThis article summarises the current literature concerning the effect of thyroid hormone disorders of mother and child and their therapy on growth.ResultsEvery untreated manifestation of congenital or acquired hypothyroidism is associated with a delay of growth and skeletal maturation. In children presenting with acquired hyperthyroidism, height is shifted towards higher values and skeletal maturation is accelerated. Approximately 20 % of children and adolescents with Down syndrome develop primary hypothyroidism, frequently manifesting within the first months of life (approximately 5.5 %). Adequate treatment of the thyroid disorder can normalise growth disorders. About 6 % of children with growth hormone deficiency develop abnormally low free thyroxin (fT4) levels in serum during growth hormone treatment due to increased conversion of T4 to T3. There is no indication for treatment after excluding secondary hypothyroidism.ConclusionsEarly diagnosis and timely, adequate treatment of thyroid function disorders of mother and child are essential to achieving growth that is as age-appropriate as possible in affected children and adolescents
Gesehen am 28.11.2018